Menyikapi Fenomena Marriage Is Scary Perspektif Qirā’ah Mubādalah - Maulydiah, Hana (Shād : Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
The marriage is scary phenomenon has recently emerged as a widely discussed issue, particularly among Generation Z who are entering the age of marriage. This anxiety is fueled by the increasing media coverage of various household problems, including infidelity, child neglect, and domestic violence (DV). This trend is further reflected in the declining marriage rate recorded in 2024. This study employs a qualitative method with documentation-based data collection and applies the qirā’ah mubādalah framework developed by Faqihuddin Abdul Qodir. A relevant related work is the study by Savira Manzilina and Ahmad Zaidinil Kamil titled “The Qur’an’s Perspective in Responding to Marriage is Scary: An Audiovisual Tafsir Analysis of Ustaz Rifky Ja’far on the YouTube Channel ‘Sayap Dakwah TV’.” Although both studies examine the marriage is scary issue, they differ in terms of analytical perspectives and methodological approaches. The findings of this research indicate that when Qur’anic verses are interpreted through the mubādalah approach, new insights emerge regarding marital relationships. This perspective offers significant contributions in addressing fear and perceived injustice often experienced by one party within a marriage. In responding to the marriage is scary phenomenon, qirā’ah mubādalah emphasizes five foundational principles of household life: commitment to a firm covenant, mutual complementarity, benevolent treatment between spouses, consultation in decision-making, and the provision of security and comfort for one another.   Keywords: Marriage is Scary, Qirā'ah Mubādalah, Generation Z, Wedding